Exploring The Influence of Homestay Attributes on Tourists’ Revisit Intentions to Tourism Village - Achlan Fahlevi Royanow; Herman; Putri Rizkiyah; Hamsu Hanafi (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2025)
This study explores the influence of homestay attributes on tourists' revisit intentions  to Kembang Kuning Tourism Village, Indonesia, following the COVID-19 pandemic and the lifting of community activity restrictions in Indonesia. This research aims to identify the specific  attributes that encourage tourists to return, emphasizing their role in revitalizing post-pandemic tourism. Data were collected using a quantitative approach by administering questionnaires to a sample of 100 respondents. The data were examined through multiple regression analysis to  determine the impact of various homestay attributes on revisit intentions. The analysis identified five homestay attributes that significantly influence revisit  intentions: Reasonable Price, Clean Room, and Local Community Life. However, attributes such  as Tourist Attractions, Building Architecture, and Security were found to have no significant  impact on tourists' decision to revisit. This study contributes to post-pandemic tourism research by  highlighting the critical attributes of homestays that drive tourists' intentions to revisit. It provides  actionable insights for homestay operators and tourism village managers to prioritize factors that increase traveler satisfaction and foster tourism revisit intention.